On-farm yield performance of improved varieties of vegetables in Sylhet region (SAARC Journal of Agriculture, 2018)
A total of five separate field trials were conducted at farm farmers’ field in Sylhet area during three consecutive crops seasons of 2014-15, 2015-16 and 2016-17, respectively to evaluate the yield performance of improved varieties with the existing cultivars of five vegetables at farmers' field. Each experiment was laid out in randomized complete block design with six dispersed replications. The unit plot size was 5m x 8m.The results showed that improved variety of tomato (var. BARI Tomato-14) produced higher average fruit (55.60 t ha-1) yield with the yield increase of 16.93% over control. In case of country bean, the local variety Goalgadda performed better and produced higher green pod yield (14.31 t ha-1) compared to that of BARI Sheem-6. The brinjal variety BARI Bt Begun-2 was the best yielder with an average fruit yield of 25.62 t ha-1 i.e. 107.62% increase over non-Bt as check. In case of yield trial with Capsicum, locally grown cultivar California Wonder performed better and produced comparatively higher yield (14.02 t ha-1) than var. BARI Mistimorich-1. In case of summer hyacinth bean viz., BARI Sheem-7 gave higher pod yield of 14.96 t ha-1 compared to that of the check variety (11.41 t ha-1) in researcher-managed trial.SAARC J. Agri., 16(1): 71-79 (2018)